Thermosensitive and antioxidant wound dressings capable of adaptively regulating TGFβ pathways promote diabetic wound healing - Hong Niu; Ya Guan; Ting Zhong; Liang Ma; Mohamed Zayed; Jianjun Guan (npj Regenerative Medicine, 2023)
Abstract Various therapies have been utilized for treating diabetic wounds, yet current regiments do not simultaneously address the key intrinsic causes of slow wound healing, i.e., abnormal skin cell functions (particularly migration), delayed angiogenesis, and chronic inflammation. To address this clinical gap, we develop a wound dressing that contains a peptide-based TGFβ receptor II inhibitor (PTβR2I), and a thermosensitive and reactive oxygen species (ROS)-scavenging hydrogel. The wound dressing can quickly solidify on the diabetic wounds following administration. The released PTβR2I inhibits the TGFβ1/p38 pathway, leading to improved cell migration and angiogenesis, and decreased inflammation. Meanwhile, the PTβR2I does not interfere with the TGFβ1/Smad2/3 pathway that is required to regulate myofibroblasts, a critical cell type for wound healing. The hydrogel’s ability to scavenge ROS in diabetic wounds further decreases inflammation. Single-dose application of the wound dressing significantly accelerates wound healing with complete wound closure after 14 days. Overall, using wound dressings capable of adaptively modulating TGFβ pathways provides a new strategy for diabetic wound treatment.